A Preliminary Study of Novel Coronavirus Disease (COVID-19) Outbreak: A Pandemic Leading Crisis in Tourism Industry of Nepal - Ulak, Nimesh (Journal of Tourism and Hospitality Education, 2020)
The aim of this paper is to explore and illuminate the preliminary impacts of novel coronavirus disease (COVID- 19) in tourism industry of Nepal. The spillover impact of pandemic has been seen in almost every sector globally. Many scholars and practitioners have already started rethinking and researching in different disciplines based on issues regarding COVID-19. Some of the disciplines are International tourism, health sector, international economy, global politics, human civilization, sustainability and so on. The United Nation World Tourism Organization (UNWTO) and World Health Organization (WHO) are closely cooperating for understanding the severe impact of escalation of coronavirus on the human health and damage in the world economy as well as tourism sector (UNWTO, 2020). There are uncountable job losses recorded in tourism industry due to stranded traveller’s mobility after many nations including Nepal declared lockdown as a strategy to control the spread of virus Therefore, devastating Airlines, shuttered borders, halt of transportation means and cancellation of rooms in hotels have a vigorous impact on tourism industry than the COVID-19 outbreak itself. It is obvious to experience changes in tourism industry; tourist’s behavior and their reluctance to travel for few years. However, travel of humans for any motives will provide spectrum to tourism mobility. The epidemic has drastically turned into pandemic as the virus has transferred to almost all the nations of the globe without visa so far.